Will genetically modified late blight resistant potatoes be the first GM crops to be approved for commercial growing in Norway? - Forbes, Edward; Wulff-Vester, Anders Keim; Hvoslef-Eide, Trine (A.K.) (Frontiers in Plant Science, 2023)
Last decade’s advances in biotechnology, with the introduction of CRISPR, have challenged the regulatory framework for competent authorities all over the world. Hence, regulatory issues related to gene editing are currently high on the agenda both in the EU and in the European Economic Area (EEA) Agreement country of Norway, particularly with regards to sustainable agriculture. During the negotiations on the EEA Agreement, Norway was allowed to retain three extra aims in the Gene Technology Act: “That the production and use of GMO happens in an ethical way, is beneficial to society and is in accordance with the principle of sustainable development”. We argue the case that taking sustainability into the decisions on regulating gene edited products could be easier in Norway than in the EU because of these extra aims. Late blight is our chosen example, as a devastating disease in potato that is controlled in Norway primarily by high levels of fungicide use. Also, many of these fungicides are being banned due to negative environmental and health effects. The costs of controlling late blight in Norway were calculated in 2006, and since then there have been new cultivars developed, inflation and an outbreak of war in Europe increasing farm input costs. A genetically modified (GM) cisgenic late blight resistant (LBR) potato presents a possible solution that could reduce fungicide use, but this could still be controversial. This paper aims to discuss the advantages and disadvantages of approving the commercial use of a GM LBR potato cultivar in Norway and compare these against currently used late blight management methods and conventional potato resistance breeding. We argue that a possible route for future regulatory framework could build upon the proposal by the Norwegian Biotechnology Advisory Board from 2019, also taking sustainability goals into account. This could favour a positive response from the Competent Authorities without breeching the European Economic Area (EEA) Agreement. Perhaps the EU could adopt a similar approach to fulfil their obligations towards a more sustainable agriculture?